Exploring the mediating effects of negative and positive religious coping between resilience and mental well-being - Surzykiewicz, Janusz; Skalski, Sebastian Binyamin; Niesiobędzka, Małgorzata; Konaszewski, Karol (Frontiers in Behavioral Neuroscience, 2022)
The purpose of the study was to examine more thoroughly the relationship between trait resilience and mental wellbeing. Although research demonstrates that this relationship is partially mediated by stress-related variables, no study has taken into account the mediating role of religious coping. We examined the mediating role of both variants of religious coping, positive and negative, along with specific strategies within the scope of religious coping strategies in a group of practicing Catholics. Participants were 317 people aged 19-60 years (M = 24.34; SD = 6.30). The respondents indicated their gender and age, and then completed the RS-14 (trait resilience), RCOPE (religious coping), and WEMWBS (mental wellbeing) scales. The results displayed a significant relationship between resilience and mental wellbeing. The relationship between resilience and positive religious coping was negligible, contrary to the relationship between resilience and negative coping that was significant but low. Although the relationships between overall negative and positive religious coping with mental wellbeing were irrelevant, we found significant relationships between some strategies and mental wellbeing. The mediation analysis has demonstrated that the general negative religious coping and the strategies of demonic reappraisal, passive religious deferral, spiritual discontent have intensified the positive relationship between resilience and mental wellbeing. Contrary to expectation, positive strategies did not mediate the relationship between resilience and mental wellbeing, except religious practices. The insignificant mediation effect can stem from the fact that the relationship between positive religious coping and stress is noticeable only in the long term. We controlled age and sex as statistically significant covariates so that the mediation effects obtained were devoid of the influence of those critical variables on the models.